2011
DOI: 10.5465/amr.2009.0318
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the Human Capital Resource: A Multilevel Model

Abstract: A balancing act: How organizations pursue consistency in routine functioning in the face of ongoing change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
1,010
4
36

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 878 publications
(1,074 citation statements)
references
References 101 publications
24
1,010
4
36
Order By: Relevance
“…Grounded on the resource-based perspective, we suggest that attracting and retaining human capital (Ployhart, 2004) can offer a strategic advantage for companies (Ployhart & Moliterno, 2011). Studies have shown that human resources management policies, many of which are now listed as I-CSR standards, can foster performance and bring about improved results at the organizational level (Aguilera et al, 2007;Cooper & Wagman, 2009;Van der Laan et al, 2008).…”
Section: Hypothesesmentioning
confidence: 97%
“…Grounded on the resource-based perspective, we suggest that attracting and retaining human capital (Ployhart, 2004) can offer a strategic advantage for companies (Ployhart & Moliterno, 2011). Studies have shown that human resources management policies, many of which are now listed as I-CSR standards, can foster performance and bring about improved results at the organizational level (Aguilera et al, 2007;Cooper & Wagman, 2009;Van der Laan et al, 2008).…”
Section: Hypothesesmentioning
confidence: 97%
“…We aggregated these individual-level pitcher wins and batter/fielder wins scores to the team level to provide an index of the quality of the team's human capital. We conceptualize human capital quality as a configural team property that captures the collective Bcan do^capa-bilities and Bwill do^motivational orientations of the team (Ployhart and Moliterno 2011). In team composition research, collective compositional characteristics are often most strongly related to performance outcomes when operationalized using the team-level mean, which provides a comprehensive representation of the distribution of composition characteristics among members (Bell 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Those characteristics that enable a team to succeed in achieving its collective goals become a property of the unit through emergence enabling processes whereby members form relationships, exchange information, and coordinate efforts commensurate with workflow structures, member interdependences, pacing requirements, and the dynamic nature of the task environment (Ployhart and Moliterno 2011). Kozlowski and Klein (2000) distinguished between two forms of emergence through which individual-level properties manifest as unit-level properties.…”
Section: Team Leader Change and Human Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…In less developed economies, financial constraints due to insufficient internal savings and strong discrimination against small firms on credit markets impede growth [Song et al, 2011] and should not be ignored. The same comment is relevant to capital adjustment costs that are important in some contexts [Foster et al, 2012] and to human capital resources [Ployhart, Moliterno, 2011]. We suppose that in developing economies such as Russia, supply-side determinants of growth, which are reflected in SME directors' perceptions of optimal scale, must be considered.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%